2015
DOI: 10.1007/978-3-319-18473-9_24
|View full text |Cite
|
Sign up to set email alerts
|

Task Allocation Approaches in Distributed Agile Software Development: A Quasi-systematic Review

Abstract: Abstract. Increasingly, software organizations are investing in distributed software development. However, this new scenario introduces a number of new challenges and risks. Organizations have sought alternatives to the traditional software development models by applying agile software development practices to distributed development. The key point in a distributed scenario is related to task allocation. This paper conducts a quasi-systematic review of studies of task allocation in distributed software develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Mak and Kruchten [20] described NextMove, a model based on the analytic hierarchy process (AHP) approach) for task assignment to remote teams in agile context. A most recently research exploring agile issues in distributed projects was developed in [21], where the authors conducted a quasi‐systematic review of studies of task allocation in DSD projects that incorporate agile practices.…”
Section: Task Assignment In Distributed Software Developmentmentioning
confidence: 99%
“…Mak and Kruchten [20] described NextMove, a model based on the analytic hierarchy process (AHP) approach) for task assignment to remote teams in agile context. A most recently research exploring agile issues in distributed projects was developed in [21], where the authors conducted a quasi‐systematic review of studies of task allocation in DSD projects that incorporate agile practices.…”
Section: Task Assignment In Distributed Software Developmentmentioning
confidence: 99%
“…Other studies, e.g. [4,6], explored task allocation in distributed agile software development contexts through literature review and proposed models indicating further studies as a promising area of research. Crowston et al 2007 [7] demonstrated the possible mechanisms of tasks allocation in community-based Free/Libre Open Source Software (FLOSS) development in self-organized volunteer teams.…”
Section: Related Workmentioning
confidence: 99%
“…Primary project management activities include managing resources, task allocation, and tracking time and budget in the best possible way [2]. Several studies have researched task allocation in global and distributed software development using traditional or agile methods [3][4][5][6]. A limited number of studies have assessed task allocation mechanisms practiced by Free/Libre Open Source Software (FLOSS) development teams; however, they did not cover commercial projects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Simão Filho et al [32] conducted a quasi-systematic review of studies of task allocation in DDS projects that incorporate agile practices. The study brought together a number of other works, allowing the establishment of the many factors that influence the allocation of tasks in DDS.…”
Section: Task Allocation In Ddsmentioning
confidence: 99%